Disability, violence, and mental health among Somali refugee women in a humanitarian setting. (2020) - Hossain, Mazeda; Pearson, Rachel; McAlpine, Alys; Bacchus, Loraine; Muuo, Sheru W.; Muthuri, Stella K; Spangaro, Jo; Kuper, Hannah; Franchi, Giorgia; Pla Cordero, Ricardo; Cornish-Spencer, Sarah; Hess, Tim; et al.
Abstract: Background: There is limited evidence on the relationship between disability, experiences of gender-based violence (GBV), and mental health among refugee women in humanitarian contexts. Methods: A cross-sectional analysis was conducted of baseline data ( n = 209) collected from women enrolled in a cohort study of refugee women accessing GBV response services in the Dadaab refugee camps in Kenya. Women were surveyed about GBV experiences (past 12 months, before the last 12 months, before arriving in the refugee camps), functional disability status, and mental health (anxiety, depression, post-traumatic stress), and we explored the inter-relationship of these factors. Results: Among women accessing GBV response services, 44% reported a disability. A higher proportion of women with a disability (69%) reported a past-year experience of physical intimate partner violence and/or physical or sexual non-partner violence, compared to women without a disability (54%). A higher proportion of women with a disability (32%) experienced non-partner physical or sexual violence before arriving in the camp compared to women without a disability (16%). Disability was associated with higher scores for depression (1.93, 95% confidence interval (CI) 0.54–3.33), PTSD (2.26, 95% CI 0.03–4.49), and anxiety (1.54, 95% CI 0.13–2.95) after adjusting for age, length of encampment, partner status, number of children, and GBV indicators. Conclusions: A large proportion of refugee women seeking GBV response services have disabilities, and refugee women with a disability are at high risk of poor mental health. This research highlights the need for mental health and disability screening within GBV response programming.